A rat model of acute kidney injury caused by multiple subcutaneous injections of Asian giant hornet (Vespa mandarina Smith) venom. (15th July 2022) - Yu, Fanglin; Cui, Long; Gao, Zhao; Lu, Xiaohan; Hu, Fengqi; Yuan, Hai
Abstract: A model of acute kidney injury (AKI) caused by multiple subcutaneous injections of Asian giant hornet ( Vespa mandarina Smith) venom was developed in male Wistar rats. The rats were injected subcutaneously at multiple sites in the dorsal region with a total venom dose of 5 mg/kg. Blood samples were obtained 8, 24 and 48 h after venom injection for the quantification of various biochemical parameters and assessment of renal function. Wasp venom caused significant increases in all biochemical parameters (aspartate aminotransferase, creatine kinase, free hemoglobin, lactate dehydrogenase, myoglobin, and plasma creatinine) within 8 h of venom administration, as well as marked alterations in renal function (a decrease in glomerular filtration rate leading to oliguria). The biochemical parameters showed varying degrees of recovery but remained elevated to varying degrees after 48 h, whereas the glomerular filtration rate showed no recovery during this period. The histopathological alterations consisted primarily of acute tubular necrosis, with tubular epithelial cell sloughing and loss of tubule brush border. This profile of biochemical and functional alterations was similar to that seen in human envenomations by this species, suggesting that this animal model may be useful for understanding the pathophysiology of AKI caused by this wasp venom. Graphical abstract: Image 1 Highlights: A model of acute kidney injury (AKI) by multiple wasp stings was established in rats. Venom caused an increase in all biochemical parameters that peaked after 8 h. Venom caused a marked, persistent reduction in glomerular filtration rate for up to 48 h. The renal histopathological changes in rats mimicked those seen in human envenomation. Wasp venom-induced AKI was apparently secondary to rhabdomyolysis and intravascular hemolysis.